Effect of an Asthma Question Prompt List and Video Intervention on Adolescents' Medication Adherence 12 Months Later. Issue 7 (July 2019) - Davis, Scott A.; Carpenter, Delesha; Lee, Charles; Garcia, Nacire; Reuland, Daniel S.; Tudor, Gail; Loughlin, Ceila E.; Sleath, Betsy
Background: Many adolescents do not obtain the maximum benefit from their asthma medications. Improving patient-provider communication may improve adolescents' asthma knowledge, adherence, and clinical outcomes.Objective: To determine how a question prompt list and educational video intervention affect youth- and caregiver-reported medication adherence and self-reported medication problems.Methods: Adolescents with persistent asthma (n = 359; 56.4% with moderate to severe asthma) and their caregivers were enrolled in a randomized controlled trial at 4 pediatric clinics. Intervention group families received a question prompt list and watched a short video before seeing the provider; control families received usual care. Youth- and caregiver-reported medication adherence was measured with a Visual Analog Scale, ranging from 0 to 100. Generalized estimating equations were used to determine how the intervention and covariates were associated with medication adherence and reported problems at 12 months.Results: The intervention was not a significant predictor of medication adherence at 12 months. Higher caregiver education was associated with higher youth-reported adherence (β = 1.1; 95% CI = 0.1, 2.1; P = 0.036) and caregiver-reported adherence (β = 1.2; 95% CI = 0.3, 2.0; P = 0.006). The intervention was associated with fewer caregiver-reported problems at 12 months (β = −0.32; 95% CI = −0.48, −0.16; P < 0.001).Conclusions and Relevance: A question prompt list and educational video decreased the number of caregiver-reported medication problems, but did not significantly affect medication adherence. Further research is needed to develop more effective interventions to improve medication adherence and outcomes.